INOVASI EDUKASI GIZI: PENDEKATAN EMOTIONAL DEMONSTRATION DALAM MENGATASI PERILAKU PICKY EATING DAN RISIKO STUNTING - Farida Wahyu Ningtyias; Sausan Sania Salsabila; Titis Azzahra Putri Auni; Syarifil Hidayatul Akbar Akbar; Inesa Malika Dewi Dewi; Nuraini Puspa Dewi Dewi (JURNAL PENGABDIAN MASYARAKAT YAMASI, 2026)
One often overlooked factor causing stunting is picky eater behavior in children. This behavior leads children to tend to choose certain foods and reject nutritious foods such as vegetables, fruits, and protein. Through an emotional and practical approach, the Emotional Demonstration (Emo-Demo) method can create a positive long-term impact. This educational activity using the Emo-Demo method aims to increase knowledge and skills in providing healthy and nutritious food for children. The activity was conducted at Posyandu Melati 2, Jambesari Village, Jambesari Darus Sholah Subdistrict, Bondowoso Regency. The target participants were 8 mothers of toddlers. Effectiveness evaluation was carried out through pre-test and post-test measurements, which showed an increase in participants' understanding of picky eater behavior as a risk factor for stunting. The Emo-Demo method proved effective, as reflected by a 75% increase in knowledge, indicating a positive impact of health promotion in improving mothers' knowledge. The Emotional Demonstration (Emo-Demo) method is effective in increasing the knowledge of mothers of toddlers regarding picky eater behavior and its relation to stunting incidence.